Evaluation of the quality of life and frequency of depressive symptoms in patients with coronary heart disease before planned coronarography - Sawicka, Julia; Jurkowska, Grażyna; Bachórzewska-Gajewska, Hanna (Przegląd Kardiodiabetologiczny/Cardio-Diabetological Review, 2008)
Introduction: Coexistence of depression and somatic disease can decrease chances to cure both diseases and worsen the prognosis. Aim: The aim of the study was to evaluate the quality of life and occurrence of depressive symptoms in patients with coronary heart disease qualified for planned coronarography. Material and methods: The study group consisted of 100 patients (both male and female) with coronary heart disease qualified for planned coronarography. The study was conducted based on the WHOQOL-100 questionnaire which evaluates the quality of life and the Beck Scale of Depression evaluating depressive mood. Results: There were 100 patients with CNS enrolled in the study including 84 persons without diabetes and 16 with diabetes. Over half (63.1%) of the patients without diabetes showed depressive symptoms of a moderate or mild severe intensity. In 43.7% of the diabetic patients included in the study mild depressive symptoms were observed. Variation of the quality of life global level was independent of the intensity of depression as well as of the occurrence or lack of diabetes. Quality of life was marked as bad by the patients in 6 categories – physical, psychological, independence, social relations, environmental relations, spiritual relations – as well as global quality of life. Clinical implications: The conducted study indicates that a significant percentage (60%) of patients qualified for coronarography show depressive symptoms of moderate or mild severe intensity. Lack of proper treatment may influence deepening of depressive symptoms along with all the consequences. This is an initial study indicating the existence of the problem of depression in patients directed to planned coronarography.